Social Network Plasticity of Mice Parental Behavior - Orikasa, Chitose (Frontiers in Neuroscience, 2022)
Neural plasticity occurs during developmental stages and is essential for sexual differentiation of the brain and the ensuing sex-dependent behavioral changes in adults. Maternal behavior is primarily affected by sex-related differences in the brain; however, chronic social isolation even in mature male mice can induce maternal retrieving and crouching behavior when they are first exposed to pups. Social milieus influence the inherent behavior of adults and alter the molecular architecture in the brain, thereby allowing higher levels of associated gene expression and molecular activity. This review explores the possibility that although the development of neural circuits is closely associated with maternal behavior, the brain can still retain its neuroplasticity in adults from a neuromolecular perspective. In addition, neuronal machinery such as neurotransmitters and neuropeptides might influence sociobehavioral changes. This review also discusses that the neural circuits regulating behaviors such as parenting and infanticide (including neglect behavior), might be controlled by neural relay on melanin concentrating hormone (MCH)–oxytocin in the hypothalamus during the positive and negative mode of action in maternal behavior. Furthermore, MCH–oxytocin neural relay might contribute to the anxiolytic effect on maternal behavior, which is involved with reward circuits.